Leaching behavior of valuable metals from by-product generated during purification of zinc electrolyte. Issue 6 (1st November 2016) - Bae, Eunok; Yoo, Kyoungkeun
Abstract: Purification cake generated during cementation process contains valuable and hazardous metals such as cadmium, copper, zinc, lead, cobalt, nickel, and antimony. The purification cake has been dumped in landfill sites, and this could cause the environmental problem such as leak of leachate and the loss of valuable metal. The present study is aimed at investigating the leaching behaviors of metals in sulfuric acid solution to recover the valuable metals. The effects of reaction time, temperature, sulfuric acid concentration, agitation speed, pulp density were investigated to establish the leaching conditions. More than 99.9% of cadmium and zinc were leached within 5 min and same ratio of cobalt was leached within 30 min. Copper, nickel, and antimony were leached 99, 97, 95%, respectively, after 60 min. Lead was detected about 2% in 60 min in 1.0 M sulfuric acid at 50 °C and 400 rpm with 10 g/L pulp density for 180 min. It is possible that lead remains as a precipitate and cadmium, zinc, copper, cobalt, nickel, antimony in leach solution are recovered.